Cytolytic Recombinant Vesicular Stomatitis Viruses Expressing STLV-1 Receptor Specifically Eliminate STLV-1 Env-Expressing Cells in an HTLV-1 Surrogate Model In Vitro - Seki, Yohei; Kitamura, Tomoya; Tezuka, Kenta; Murata, Megumi; Akari, Hirofumi; Hamaguchi, Isao; Okuma, Kazu (Viruses, 2022)
Human T-cell leukemia virus type 1 (HTLV-1) causes serious and intractable diseases in some carriers after infection. The elimination of infected cells is considered important to prevent this onset, but there are currently no means by which to accomplish this. We previously developed “virotherapy”, a therapeutic method that targets and kills HTLV-1-infected cells using a cytolytic recombinant vesicular stomatitis virus (rVSV). Infection with rVSV expressing an HTLV-1 primary receptor elicits therapeutic effects on HTLV-1-infected envelope protein (Env)-expressing cells in vitro and in vivo. Simian T-cell leukemia virus type 1 (STLV-1) is closely related genetically to HTLV-1, and STLV-1-infected Japanese macaques (JMs) are considered a useful HTLV-1 surrogate, non-human primate model in vivo. Here, we performed an in vitro drug evaluation of rVSVs against STLV-1 as a preclinical study. We generated novel rVSVs encoding the STLV-1 primary receptor, simian glucose transporter 1 (JM GLUT1), with or without an AcGFP reporter gene. Our data demonstrate that these rVSVs specifically and efficiently infected/eliminated the STLV-1 Env-expressing cells in vitro. These results indicate that rVSVs carrying the STLV-1 receptor could be an excellent candidate for unique anti-STLV-1 virotherapy; therefore, such antivirals can now be applied to STLV-1-infected JMs to determine their therapeutic usefulness in vivo.